PENURUNAN ANGKA KUMAN PADA PERALATAN MAKAN DENGAN MENGGUNAKAN EKSTRAK BUAH BELIMBING WULUH (AVERRHOA BILIMBI) - Nurafni Maftukhah (jurnal kesehatan terapan sains dan teknologi, 2023)
Background: The cutlery used by traders is one of the factors that plays an important role in the transmission of disease, such as the cleanliness of the stall and the location of the stall, the process of washing cutlery does not meet health requirements. The requirement for cutlery should not have a germ count of <0 colonies/cm2. Objectives: To determine the effectiveness of star fruit extract (Averrhoa bilimbi) in reducing the number of germs on eating utensils. Method: This research is experimental or experimental (experiment research) using 4 repetitions and 5 treatments, namely concentrations of 10.0%, 12.5%, 15.0%, 17.5%, 20.0% which are used for the disinfectant process. Results: The results showed that the measurement of the germ count in the control was 17.5×103 cfu/ml, at a concentration of 10.0% the average reduction in the germ rate was 60.9%, at a concentration of 12.5% the average reduction in the germ rate was 90.8%, at a concentration of 15.0% the average reduction in germ numbers was 90.9%, at a concentration of 17.5% the average reduction in germs was 71.7%, at a concentration of 20.0% the average reduction in germs was 89.8% . Statistical test results obtained P-Value = 0.032 meaning at alpha 0.05 it can be concluded that there is an effect after administration of star fruit extract (Averrhoa bilimbi) on reducing the number of germs. Conclusion: There was an effect after being given a solution of star fruit extract (Averrhoa bilimbi) to reduce the number of germs on cutlery before and after at various 5 concentration variations.